TINJAUAN OVERLAPPING TUPOKSI ORGANISASI PERANGKAT DAERAH DALAM PENERAPAN PP 41 TAHUN 2007 (STUDI KASUS PADA ORGANISASI PERANGKAT DAERAH KOTA SUKABUMI) - Rr. Harida Indraswari,, Yudiantarti Safitri (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
This study aims at identifying the implementation of the Sekretariat Daerah functions based on the suitability formulation of basic tasks and duties. It also analyzes the possibility of work overlapping between Sekretariat Daerah and other local agencies that act as auxiliary units such as Bappeda, BKD, Inspectorate and core units (dinas) as the provider of public service. Thisstudy takes place in Kota Sukabumi. It employs a qualitative approach, where primary data are obtained through questionnaires, in-depth interviews and focused group discussions, while secondary data are obtained through textbooks, regulation and relevant documents. It uses purposive sampling technique in determining the key informant. Those data are analyzed qualitatively with data triangulation technique. The results show that there are overlapping functions among some local agencies in Kota Sukabumi that will lead to expansion of organization size. Another existing problem is the lack of clarity about the responsibilities of the organizations with similar core duties, which eventually leads to confusion at the time of duties execution in the field. The local government (Kota Sukabumi) should consider the needs of organization carefully when formulating core duties that can be obtained through the analysis of workload, job analysis and Standard Operating Procedure (SOP).